2021
DOI: 10.5296/ijafr.v11i2.18634
|View full text |Cite
|
Sign up to set email alerts
|

Does Sticky Cost Behavior Affect Earnings Quality? Evidence From Egypt

Abstract: This paper seeks to extend the literature on cost behavior by providing additional evidence on sticky cost behavior in developing countries namely Egypt. Moreover, it aims to determine to what extent sticky cost behavior affects earnings quality. The paper depends on a sample consists of 38 listed firms in the Egyptian Exchange over the period from 2004 to 2017. The findings reveal that total costs respond asymmetrically to the equivalent change in sales in six of the nine examined sectors. Furthermore, both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Additional evidence on asymmetric cost behavior in Egyptian sectors was offered by Wahdan et al (2021). The findings showed that six of the nine sectors examined had sticky cost behavior.…”
Section: Cost Stickiness In Egyptmentioning
confidence: 95%
“…Additional evidence on asymmetric cost behavior in Egyptian sectors was offered by Wahdan et al (2021). The findings showed that six of the nine sectors examined had sticky cost behavior.…”
Section: Cost Stickiness In Egyptmentioning
confidence: 95%
“…‫ب‬ ‫تئكةب‬ ‫تااباثس‬ ‫تثمبا‬ ‫أ‬ ‫،بك‬ ‫.ب‬ ‫ت‬ ‫ثثى‬ ‫يمباث‬ ‫تثم‬ ‫باثفع‬ ‫تكا‬ ‫ب‬ ‫ت‬ ‫كئ‬ (Saleh et al, 2018, Faisal 2021, Wahdan et al, 2021, Abdullah 2020) ‫ظب‬ ‫تفق‬ ‫الباث‬ ‫تاتم‬ ‫تثاجبفع‬ ‫ب‬ ‫ت‬ ‫تئكةبكئ‬ ‫تااباثس‬ ‫تثلبا‬ ‫عكثس‬ ‫با‬ ‫ت‬ ‫تميبكئ‬ ‫تثلبأت‬ ‫اس‬ ‫تزلبام‬ ‫تثبمك‬ ‫.بك‬ ‫.ب‬ ‫تب‬ ‫قثس‬ ‫اث‬ (Banker et al, 2016, Maghsoud and (Costa 2020, Ciftci 2016, Wahdan et al, 2021, Salhi et al, 2018, Thomas and Teru 2020, Hertlieb and Lay 2022, Silva 2019, Kontesa and Brahmana 2018, Mahdavinia and Zolfagheri 2017 . ‫قثسبى‬ ‫ثلباث‬ ‫عئك‬ ‫بثئ‬ ‫ى‬ ‫اثعى‬ ‫ب‬ (Abdelhy et al, 2021, Mardani et al, 2020, Dickinson et al, 2018, Habib and Hasan 2019, Habib and Hasan 2017, Shahzad et al, 2019 (Collins et al, 2022, Para and Dobo, 2021, Hossain, 2021, Rahman and Liu, 2021, Ogbodo and Benjamine 2021, Bankole and Isreal, 2020, Azar et al, 2019…”
Section: ‫البحث‬ ‫ممخص‬mentioning
confidence: 99%
“…Chen, et al, 2012;Hartlieb,, et al, 2020) (Le, et al, 2022) ‫لبيب‬ ‫زكي‬ ‫المنعم‬ ‫عبد‬ ‫محمد‬ ‫خالد‬ ‫عمر‬ ‫د.‬ ‫اإلدارة‬ ‫بمجلس‬ ‫البشري‬ ‫الجنس‬ ‫تنوع‬ ‫أثر‬ ‫وفعالية‬ ‫الرقابة‬ ‫نظم‬ 119 ‫ال‬ ‫التحاد‬ ‫والمراجعة‬ ‫المحاسبة‬ ‫مجلة‬ ‫العربية‬ ‫جامعات‬ ‫الثالث‬ ‫العدد‬ 2023(Chae & Chung, 2015Hussien, et al, 2021;Kim, et al, 2022) (Ibrahim, et al, 2022) ‫لبيب‬ ‫زكي‬ ‫المنعم‬ ‫عبد‬ ‫محمد‬ ‫خالد‬ ‫عمر‬ ‫د.‬ ‫اإلدارة‬ ‫بمجلس‬ ‫البشري‬ ‫الجنس‬ ‫تنوع‬ ‫أثر‬ ‫وفعالية‬ ‫الرقابة‬ ‫نظم‬ 120 ‫ال‬ ‫التحاد‬ ‫والمراجعة‬ ‫المحاسبة‬ ‫مجلة‬ ‫العربية‬ ‫جامعات‬ ‫الثالث‬ ‫العدد‬ 2023(Mary & Okelue, 2012Warganegara & Tamara, 2014;Kontesa & Brahmana, 2018) e.g. Li, 2018;Wahdan, et al, (Noreen, 1991) (Anderson, et al, 2003) Anderson, et al, (2003 Asymmetric cost behavior (Dierynck, et al, 2012) Adjustment costs Weiss, 2010;Pervan & Pervan, 2012) Cost anti-stickiness (e.g. Weiss, 2010;Pervan & Pervan, 2012) Agency theory (Jensen & Meckling, 1976) Real options theory (Dixit & Pindyck, 1994) Empire building motives (Hope & Thomas, 2008;Chen, et al, 2012;Sayrani, et al, 2016) (Chen, et al, 2012) (Dierynck, et al, 2012;Kama & Weiss, 2013) (Dixit & Pindyck, 1994) ‫لبيب‬ ‫زكي‬ ‫المنعم‬ ‫عبد‬ ‫محمد‬ ‫خالد‬ ‫عمر‬ ‫د.‬ ‫اإلدارة‬ ‫بمجلس‬ ‫البشري‬ ‫الجنس‬ ‫تنوع‬ ‫أثر‬ ‫وفعالية‬ ‫الرقابة‬ ‫نظم‬…”
unclassified
“…Chen, et al, 2012;Kwon, 2018;Lopatta, et al, ‫العدد‬ 2023‫العدد‬ Huang, et al, (2017 ) (e.g. Li, 2018;Da Silva, et al, 2019;Wahdan, et al, (e.g. Chen, et al, 2012;Xue & Hong, 2016;Hartlieb,, et al, 2020) (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation